2015
DOI: 10.1080/09669582.2015.1027213
|View full text |Cite
|
Sign up to set email alerts
|

Climate change mitigation and the age of tourism accommodation buildings: a UK perspective

Abstract: Recent research on climate change mitigation has emphasized decision-making within tourism businesses is vital for sustainable futures. However, there has been little consideration of how the age of buildings and (historic) property frames,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…This article focuses on the adoption of renewable energy innovations by consumers, notably by the owners/ managers of tourist accommodation establishments. 1 Research carried out in Europe and beyond has shown that the adoption of renewable energy innovations or renewable energy technologies in hotels and other types of tourist accommodation is low, namely between 6% and 25%, and the highest rate is for solar thermal panels (Coles, Dinan and Warren, 2015;Dalton, Lockington and Baldock, 2007;Karagiorgas et al, 2006;Knezevic and Vicic, 2008;Knowles et al, 1999). A review of the literature identifies several factors that influence the uptake of renewable energy in hotels.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This article focuses on the adoption of renewable energy innovations by consumers, notably by the owners/ managers of tourist accommodation establishments. 1 Research carried out in Europe and beyond has shown that the adoption of renewable energy innovations or renewable energy technologies in hotels and other types of tourist accommodation is low, namely between 6% and 25%, and the highest rate is for solar thermal panels (Coles, Dinan and Warren, 2015;Dalton, Lockington and Baldock, 2007;Karagiorgas et al, 2006;Knezevic and Vicic, 2008;Knowles et al, 1999). A review of the literature identifies several factors that influence the uptake of renewable energy in hotels.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By adopting these measures, these economies can make humans and cities safer, more resilient, and more sustainable. Tourism growth can help to ensure sustainable production and consumption patterns and contest the impacts of climate change (Coles et al 2015;Danish,, and Wang, Z. 2018;Fitchett et al 2017;Gössling and Peeters 2015;Yu et al 2019).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In particular, an MMR study may simultaneously answer both qualitative and quantitative research questions. For example, Coles et al (2015) examined the relationships between hotel property age, energy use and environmental innovations, and they had two objectives. Quantitatively, they explored business owners’ perceptions of the relationship between business and the environment, their environmental practices and operating characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Many destinations are thus modernising and adapting their management systems to satisfy complex consumer demands (Mehran and Olya, 2018) and local communities’ expectations (Nunkoo et al , 2013). At the macro level, destinations are facing many global mega-trends such as climate change, rising inequality and the changing nature of work (Coles et al , 2015). These issues and challenges are complicated, interconnected and involve multiple interacting systems; they thus require methodologies that can fully appreciate and critically analyze the plurality of all positions, practices and insights.…”
Section: Discussionmentioning
confidence: 99%